1990
DOI: 10.1177/109019819001700308
|View full text |Cite
|
Sign up to set email alerts
|

Essential Elements of Self-Help/Minimal Intervention Strategies for Smoking Cessation

Abstract: Two decades of research suggest that self-help/minimal intervention strategies for smoking cessation may be the preferred means by which smokers stop and can produce success rates approximating those of more formal programs, at lower cost and with greater access to relevant populations. In order to make the best possible use of these self-help/minimal intervention approaches, the National Cancer Institute (NCI) supported a series of randomized, controlled intervention trials and, in June of 1988, convened an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
67
0
3

Year Published

1990
1990
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(70 citation statements)
references
References 18 publications
0
67
0
3
Order By: Relevance
“…This is comparable with other studies of self-help interventions (Curry, 1993) as well as the results reported by Schneider and colleagues (1990). Additional progress toward the goal of cessation was suggested by a 75% increase over baseline in participants' reported intention to quit smoking, which is considered to be a primary goal of minimal contact=self-help interventions (Glynn, Boyd, & Gruman, 1990).…”
Section: Internet-enabled Help For Smoking Cessation 37mentioning
confidence: 99%
“…This is comparable with other studies of self-help interventions (Curry, 1993) as well as the results reported by Schneider and colleagues (1990). Additional progress toward the goal of cessation was suggested by a 75% increase over baseline in participants' reported intention to quit smoking, which is considered to be a primary goal of minimal contact=self-help interventions (Glynn, Boyd, & Gruman, 1990).…”
Section: Internet-enabled Help For Smoking Cessation 37mentioning
confidence: 99%
“…[11][12][13][14][15][16] Current recommendations are that minimal smoking cessation interventions be incorporated in routine primary health care and that these interventions include, as a minimum, provider advice to quit smoking and written material or other help for quitting. [17][18][19] Most health professionals are aware and approve of these recommendations and report applying them to many of their patients. [20][21][22] However, studies show that smoking cessation interventions are not consistently delivered to patients.…”
mentioning
confidence: 99%
“…Existen una serie de ventajas potenciales de los tratamientos de autoayuda con manual, entre las que se incluye un mayor mantenimiento de los efectos del tratamiento (Glasgow, Schafer y O'Neill, 1981), lo cual es de vital importancia, puesto que la recaída constituye el principal problema de todas las conductas adictivas. Otras ventajas de la utilización de manuales son (Curry, 1993): 1) la posibilidad de ser aplicados por personal no especializado; 2) distribución a un bajo coste en una variedad de contextos; 3) se pueden elaborar para diferentes poblaciones diana (p.ej., basándose en el estadio de cambio o en características específicas de los fumadores); 4) los fumadores pueden adapteu-el programa a sus necesidades específicas (por ejemplo, variar el orden en que se realicen los ejercicios recomendados), pueden seguirlo a su ritmo y terminarlo más tarde; 5) por la posibilidad de guardar los materiales escritos, los fumadores, que fracasan en su intento de abandono del tabaco, pueden repetir con facilidad el programa (Glynn, Boyd y Gruman, 1990a) y, en caso de haber conseguido la abstinencia y experimentar momentos de tentación o consumos puntuales, se pueden utilizar para trabajar la motivación y reafirmarse en la decisión de mantenerse abstinente.…”
Section: Los Programas De Autoayuda Con Manualesunclassified
“…Vcirios expertos han indicado que los manuales para dejar de fumar deberí-an adaptarse a las características sociodemográficas, culturales y relacionadas con fumar de los fumadores (p.ej., Strecher, Rimer y Monaco, 1989; Glynn et al, 1990aGlynn et al, ,1990b, pues ello contribuiría a lograr porcentajes de abstinencia más altos que con los manuales estándar. Esto ha derivado en la realización de estudios utilizando la adaptación de los materiales, a través de distintos procedimientos, a poblaciones específicas de fumadores.…”
Section: Los Programas De Autoayuda Con Manualesunclassified